Stochastic short-term mine scheduling targeting stationary grades - Augusto Andres Torres Toledo; João Felipe Coimbra Leite Costa; Luciano Nunes Capponi; Diego Machado Marques (REM: International Engineering Journal)
Abstract One of the key objectives in short-term mine planning is to establish a sequence of contiguous blocks organized into diglines, each characterized by consistent low-grade variability and minimal fluctuations, ensuring a stable output. This practice guarantees a steady and reliable supply of ore to the processing plant across various operational phases, each phase outlined for clarity. The creation of this digline requires the generation of multiple random models and involves choosing a model whose grade histogram aligns closely with the predefined criteria. In stochastic mine planning, geological uncertainty and transfer functions are employed to propagate the risk into the mining schedule focusing on grade control. This is accomplished by opting for blocks that present the lowest risk associated with grade uncertainty, a process enhanced by prioritizing blocks situated in geopositions with a proven high probability of occurrence. This study unveils detailed simulation models, clearly outlined digline selection methodologies, and a thorough optimization process, each aspect exemplified within the practical context of a phosphate mine. Our findings confirm the viability of this approach in real industry practice.